Impact of passenger car NOX emissions on urban NO2 pollution – Scenario analysis for 8 European cities. (December 2017) - Degraeuwe, Bart; Thunis, Philippe; Clappier, Alain; Weiss, Martin; Lefebvre, Wouter; Janssen, Stijn; Vranckx, Stijn
Abstract: Residents of large European cities are exposed to NO2 concentrations that often exceed the established air quality standards. Diesel cars have been identified as a major contributor to this situation; yet, it remains unclear to which levels the NOX emissions of diesel cars have to decrease to effectively mitigate urban NO2 pollution across Europe. Here, we take a continental perspective and model urban NO2 pollution in a generic street canyon of 8 major European cities for various NOX emission scenarios. We find that a reduction in the on-road NOX emissions of diesel cars to the Euro 6 level can in general decrease the regional and urban NO2 concentrations and thereby the frequency of exceedances of the NO2 air quality standard. High NO2 fractions in the NOX emissions of diesel cars tend to increase the urban NO2 concentrations only in proximity of intense road traffic typically found on artery roads in large cities like Paris and London. In cities with a low share of diesel cars in the vehicle fleet such as Athens or a high contribution from the NO2 background to the urban NO2 pollution such as Krakow, measures addressing heavy-duty vehicles, and the manufacturing, energy, and mining industry are necessary to decrease urban air pollution. We regard our model results as robust albeit subject to uncertainty resulting from the application of a generic street layout. With small modifications in the input parameters, our model could be used to assess the impact of NOX emissions from road transport on NO2 air pollution in any European city. Highlights: NO2 is modelled for different diesel car NOx emissions and NO2 fractions in a street canyon in 8 EU cities. We consider the changes in European, regional and local street canyon emissions. Air quality would benefit from compliance of diesel cars with Euro 6d under real-driving conditions. High NO2 fractions impact the exceedance of the hourly limit value of 200 μg/m 3 .